European security in a post-Brexit world - Paladini, Stefania; Castellucci, Ignazio (Brexit studies series, 2019)
The security agenda in the Europe Union is linked to the member states' abilities to work together. This book explores a series of post-Brexit scenarios in an attempt to understand what Brexit will mean for the European Union in terms of its security.